The Effect of Local Wisdom Values on Employee Performance in Regional General Companies (PERUMDA) Tirta Karajae City of Parepare - Alfian Mukti Fajar; Ananda Putri; Rahma Amariaman; Irwan Idrus; Bahruddin (www.amertainstitute.com, 2023)
Many people think that there has been a degradation or loss of local wisdom values inherited by their ancestors inthe form of mental attitudes that are full of morality-based values, such as the nature of Getteng (assertiveness), Lempu (honesty) and Ada Tongeng (the only one). words and actions), all of which are summarized in a package of cultural attitudes (Cultural Attitude) that is upheld, namely Siri (Highest Honor). ' and Getteng on Employee Performance at the Tirta Karajae Regional Public Company (PERUMDA) office, Parepare City. Respondents who were used as samples in the study after calculating the slovin formula were 90 people.The method used in this study is a quantitative model approach where data is obtained through questionnaires and will then be processed using the SPSS application. The results of the analysis obtained show that the value of local wisdom of Lempu and Getteng has a negative but not significant impact on employee performance, while the value of Siri' local wisdom has a positive and significant effect on employee performance at the Tirta Karajae Regional Public Company (PERUMDA) Parepare City.